Ionic Liquid Mediated Synthesis of Novel tetrahydroimidazo [1,2- a]pyrimidine-6-carboxylate Derivatives - V. Thorat, Vinod; A. Dake, Satish; U. Deshmukh, Satish; Rasokkiyam, Elayaraja; Farees Uddin, Mohd.; P. Pawar, Rajendra (Letters in Organic Chemistry, 2013)
A novel route for the synthesis of tetrahydroimidazo [1,2-a] pyrimidine-6-carboxylate derivatives in presence of 1-ethyl-3-methyl imidazolium hydrogen sulphate ionic liquid at room temperature has been reported via Biginelli reaction. The process offer several advantages such as short reaction time, excellent yield of products, simple work up procedure etc. 1-ethyl-3-methyl imidazolium hydrogen sulphate ionic liquid is utilized as solvent system and catalyst to enhance the rate of reactions.
Keywords: 5-dihydro-1H-pyrazole-4-carbonitrile